Pengaruh Pendidikan Kesehatan Metode Brainstorming dan Video terhadap Pengetahuan tentang Demam Berdarah pada Keluarga di Wilayah Kerja Puskesmas Puger Kabupaten Jember (The effect of Health Education Brainstorming Method and Video to the Knowledge about - Mukhammad Syafi`udin; Wantiyah Wantiyah; Kushariyadi Kushariyadi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
The increasing cases of dengue hemorrhagic fever disease in both children and adults can beinfluenced by several factors. One of that influences increasing of dengue fever is lack of communityknowledge about dengue hemorrhagic fever. Brainstorming is a form of discussion to gather theinformation from all participants. This research was to find out the effect of health educationbrainstorming method and video toward knowledge of dengue fever in the work area of Puger PublicHealth Center the distric of Jember. This was a quasy experiment research with two groups pretestposttesttreatment design. The population were 88 families with 30 respondents as sample,conducted by simple random sampling, and divided into two groups 15 respondents as treatmentgroup and 15 respondents as control group. Treatment group got health education brainstormingmethod combined with video and control group got health education brace method. Data wereanalyzed used t-test dependent and t-test independent with 95% CI (α: 0,05). The result showedthere were significant differences of knowledge before and after in both treatment group and controlgroup (p: 0,000) and there were significant differences between treatment group and control afterhealth education (p: 0,001). Overall, health education by brainstorming method and can improveknowledge of dengue hemorrhagic fever. It is recommended for nurses to do health educationpreventation and treatment about dengue hemorrhagic fever to improve knowledge people.Keywords: health education brainstorming method and video, knowledge, dengue hemorrhagicfever